Monthly Video-Consultation for Children With Type 1 Diabetes Using a Continuous Glucose Monitoring System: Design of ViDiKi, a Multimethod Intervention Study to Evaluate the Benefit of Telemedicine. (January 2020) - Frielitz, Fabian-Simon; Müller-Godeffroy, Esther; Hübner, Joachim; Eisemann, Nora; Dördelmann, Jana; Menrath, Ingo; Katalinic, Alexander; Hiort, Olaf; von Sengbusch, Simone
Background: The introduction of continuous glucose monitoring (CGM) implies new challenges for diabetes care. As CGM systems are often directly linked to a web-based software solution, structured telemedicine care using a video-consultation may be a new option for families who care for children with type 1 diabetes mellitus (T1DM). Methods: "ViDiKi" (Virtual Diabetes Outpatient Clinic for Children and Youth) is a multicenter controlled trial carried out in Northern Germany. ViDiKi will examine if monthly telemedical consultations, in addition to regular care, will improve glycemic control and psychosocial outcomes. The primary outcome is glycemic control as measured by a change in glycated hemoglobin (HbA1c). A total of 240 participants aged between one year and 16 years using a CGM with multiple daily injections (MDI) or insulin pump therapy were recruited and assigned to a starter group or a six-month waiting control group. The sample size is designed to detect a between-group difference of 0.5% in HbA1c change at six months. Secondary outcomes are variability of blood glucose, health-related quality of life, self-efficacy, and satisfaction with telemedicine. To gain deeper insight into the experience of using telemedicine, qualitative interviews will be conducted. In a health-economic analysis, the costs of telemedicine and a cost-of-care analysis will be calculated. Conclusions: The results from the ViDiKi study shall give important information on the feasibility and putative benefits of telemedicine in children with T1DM and their caregivers. German Clinical Trails Register (DRKS): DRKS00012645